Hydrogen product of gasification of sawdust. (Journal of Basic and Applied Research in Biomedicine, 2022)
A theoretical experimental work is developed for the production of gas rich in hydrogen content, based on a model of isothermal gasification of sawdust pellets in a reactor in a fluidized bed regime, simulated through an application in Matlab environment, analyzing in particular the influence of the operating temperature in the range 750 °C-850 °C, oxidizing / fuel ratio (for air and steam) and obtaining kinetic parameters. The simulation model presents good agreement with the experimental values, showing the increase of the hydrogen content with the increase of the temperature as with the greater reducing atmosphere and with the introduction of steam in the process.